Cooperation and Social Rules Emerging From the Principle of Surprise Minimization - Hartwig, Mattis; Peters, Achim (Frontiers in Psychology, 2021)
The surprise minimization principle (i.e. the free energy principle) offers a modern perspective in cognitive science. Individual human behaviors have already been investigated under the surprise minimization: perceptual and active inference, decision making, exploration, etc. However, surprise minimization has not yet been applied in a multi-agent setup. This is, to the best of our knowledge, the first paper that explains the emergence of cooperation and social rules through the surprise minimization framework. Our conceptual analysis shows under which circumstances cooperation becomes likely and when not. We further show that in social decision-making, surprise minimization is superior in many aspects to the classical approach of maximizing utility. Finally, we show that surprise minimization – but not classical utility maximization – can be used to explain why policy makers who carefully balance utility maximization and freedom of choice can reduce toxic, disease-causing stress in human societies. In this interdisciplinary research field, we include concepts from computational neuroscience, psychology, sociology and medicine to apply them in the multi-agent setup and explain cooperative aspects in social behavior. In this way, this analysis opens a new research perspective.